Participatory Approach to Indonesian Rural Development in the Era of Reformation - Venus, Antar (Mediator, 2001)
The approach used by the government for developing society both rural and urban for the last 30 years has been the mobilization approach with top-down communication patterns. This approach does not give a space to the people to participate in the development process. When people become critical and aware of their own rights, a democratic participation approach to the development is needed. Such an approach, called the participatory development approach, is assumed to be able to give a space to the people to participate and to decide what are the best for themselves. The implementation of this approach in Indonesia is appropriate due to the reason that such an approach is in accordance with the principle of social justice.